Intelligent Pool Decision System Using Zero-Order Sugeno Fuzzy System - Chua, Shing Chyi; Wong, Eng Kiong; Koo, Voon Chet (2005)
This paper describes the approach of using the zero-order Sugeno fuzzy system to design an intelligent decision system for a game of pool. The decision system consists of three types of playing strategies for a normal game of pool: direct, combination and bank shots. For each of the playing scenario on the pool table, the decision system comes out with one output shot (or best shot): presenting which ball should be chosen and which path should it follow. The system has been tested step-by-step on a real pool game and results are tabulated in the paper. The decision is designed as the brain for a robotic pool system.